Ecological assessment of the reintroduced milky stork population in Malaysia - Abdul Rahman, Mohd Faid (2017)
Throughout time, the deterioration of natural habitat and its quality has driven many wildlife species close to extinction. The Milky stork (Mycteria cinerea) is one important example for this worsening trend. Its conservation status was recently up-listed to ‘threatened’ from ‘vulnerable’ by the IUCN in 2016. Nevertheless, the country still has a good number of captive-bred populations in its possession which were later re-introduced back into the wild. This study was done in a hope to understand the Milky stork’s ecology in Malaysia following the reintroduction programme. It consisted of researches conducted during pre and post-release period which are: 1) understanding the Milky stork’s ecology pre-release or in captivity in Zoo Negara using bio-logging technique (and its feasibility to be used in the field); 2) understanding the Milky stork’s ecology and adaptability post-release in Kuala Gula; 3) assessment of the Milky stork’s habitat quality in relation to heavy metals and glyphosate pollution and last but not least; 4) understanding the risk of exposure of the Milky stork population to the available pollutants particularly heavy metals using Exposure Model Analysis. As for the results, the use of bio-logging technique helped to predict the Milky stork’s activity and movement (temporal and spatial movements) following the reintroduction programme. In pre-release study, important sites associated with the Milky storks’ breeding, foraging and roosting activities have been identified and their utilization are discussed in the thesis. For the habitat quality study, the risk of the population being exposed to Zn, Cd and Pb was calculated. To compare, the exposure dose for all metals are much lower in water (0.009 - 0.01 mg kg-1d-1) compared the foods (0.30 – 1.49 mg kg-1d-1). This suggests that the Milky storks are more likely to accumulate higher amount of Zn, Cd and Pb through food intake (> 90% of exposure) although their levels are still within the acceptable limit. Glyphosate from surface sediments in the Milky stork’s foraging areas was found to range between 0.26 and 1.80 mg kg-1 which is considered low and thus no immediate threat to the Milky stork’s environment. To conclude by objectives: 1) bio-logging technique has been proven to be an effective tool or technique in studying the Milky stork’s behavior albeit several modifications to the logger and field testing are still needed before it can be fully employ to study the population in the wild; 2) The reintroduced Milky storks were able to adapt very well to the new environment in Kuala Gula by taking advantage on the different types of habitat available (natural and artificial) particularly during foraging. However, the population still facing difficulty in selecting appropriate nesting or breeding area due to the rapid development of Kuala Gula’s coastal environment; 3) The pollutants level in Kuala Gula’s environment i.e. heavy metals and glyphosate are still considered as low but the increasing trend of the metals need to be regulated; 4) The Milky stork’s population risk of being exposed to heavy metals (through diet) are still low yet again, authority needs to continuously monitor the environment’s quality due to the increasing pattern of metals level mentioned in the study. The findings also point towards the need for urgent protection and conservation of the Milky stork’s habitats. Several recommendations are also given to help improve the reintroduction programme.